THE CASE OF SUCCESSFUL SURGICAL TREATMENT OF INTRAUTERINE DEVICE MIGRATED INTO THE PELVIC CAVITY - О. NEMATZODA; М.М. МАRIZOEVA; D.А. RAHMONOV; SH.SH. АМОNOV; F.B. BOKIEV; U.S. ISMATOVA (Avicenna Tajik State Medical University, 2017)
The article presents the results of timely diagnosis and successful surgical treatment of the patient with intrauterine device (IUD) migrated into the pelvic cavity. The period of IUD implantation lasted 10 days. Hospital visit was caused by increasing of the pain intensity in small pelvis and the appearance of dysuric phenomena. Ultrasound investigation detected that the migration of the intrauterine device occurred through the left fallopian tube. The end of the intrauterine device thread was located in the lumen of the left fallopian tube. Ultrasound signs of the IUD were manifested by hyperechoic and relatively long structure with the acoustic shadows. The IUD was not detected in the uterine cavity during gynecological examination. For more accurate topical diagnosis of the migrated IUD the patient underwent radiography of the abdominal cavity and small pelvis and the dislocation of the IUD was confirmed. The surgery of the patient was performed through laparoscopic approach. The intraoperative complications were not detected. The surgery lasted for 35 minutes. The drainage tube was removed on the second postoperative day. Antibiotics, nonsteroidal anti-inflammatory drugs and spasmolytics were prescribed to the patient postoperatively. The length of hospital stay was 4 days. Follow-up period in one and three months determined a lack of any complaints in the patient.